Trust blog ranking using multi-criteria decision analysis AHP and TOPSIS - binti Mohd Zulkefli, N.A. (Springer Verlag, 2017)
Following the lack of trust for information description and trust support for the query processing, traditional blog systems are unable to satisfy users in terms of the performance of information organisation and retrieval. As well as the fact that the information provided by the website is undefined trust and a user keeps on searching the information from the internet, it is important for a user to have some belief or trust in the information they had read. The multi criteria decision making technique (MCDM) through the integration of the analytic hierarchy process (AHP) and technique for order preference by similarity to ideal solution (TOPSIS) method is introduced to provide the trusted score for ranking the blog based on the blog trustworthiness level. Our MCDM methods are developed to consider the important keys of trusted information, which entail great agreement from experts based on the proposed criteria which are the follower, viewer and post. We present experimental results that can beneficially be used by the user whenever they are looking for the blog information and they can manage to rank the result based on the trusted score value. © 2018, Springer Nature Singapore Pte Ltd.